Defective p27 phosphorylation at serine 10 affects vascular reactivity and increases abdominal aortic aneurysm development via Cox-2 activation. (March 2018) - Molina-Sánchez, Pedro; Del Campo, Lara; Esteban, Vanesa; Rius, Cristina; Chèvre, Raphael; Fuster, José J.; Ferrer, Mercedes; Redondo, Juan Miguel; Andrés, Vicente
Abstract: Phosphorylation at serine 10 (S10) is the major posttranslational modification of the tumor suppressor p27, and is reduced in both human and mouse atherosclerosis. Moreover, a lack of p27-phospho-S10 in apolipoprotein E-null mice (apoE−/−) leads to increased high-fat diet-induced atherosclerosis associated with endothelial dysfunction and augmented leukocyte recruitment. In this study, we analyzed whether p27-phospho-S10 modulates additional endothelial functions and associated pathologies. Defective p27-phospho-S10 increases COX-2 activity in mouse aortic endothelial cells without affecting other key regulators of vascular reactivity, reduces endothelium-dependent dilation, and increases arterial contractility. Lack of p27-phospho-S10 also elevates aortic COX-2 expression and thromboxane A2 production, increases aortic lumen diameter, and aggravates angiotensin II-induced abdominal aortic aneurysm development in apoE−/− mice. All these abnormal responses linked to defective p27-phospho-S10 are blunted by pharmacological inhibition of COX-2. These results demonstrate that defective p27-phospho-S10 modifies endothelial behavior and promotes aneurysm formation via COX-2 activation. Graphical abstract: Highlights: p27-phospho-S-10 modulates vasoconstriction and endothelial-dependent vasodilation in thoracic aorta and arterioles via COX-2. Defective p27-phospho-S10 induces outward remodeling in thoracic aorta without affecting blood pressure. Defective p27-phopho-S10 promotes abdominal aortic aneurysm formation via COX-2 activation.